Overview Of Psychological Well-Being In First-Year Students of STIKes Santa Elisabeth Medan - Ernita Rante Rupang; Friska Sembiring; Eka Olivia Togatorop (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Students are those who pursue knowledge or who study in college. Students who cannot accept the shortcomings that exist in themselves will often feel stressed because these individuals have not been able to adapt to their new environment, so they need good psychological well-being. So in this case it makes the individual feel that he cannot respect himself, then a high psychological well-being is required. Objectives: The purpose of this study was to describe psychological well-being in level 1 students of STIKes Santa Elisabeth Medan. Methods: The research design is descriptive with a cross-sectional approach. The sample of this research was 206 level 1 students of STIKes Santa Elisabeth Medan using a total sampling technique. The measuring instrument for this study used a psychological well-being questionnaire with six dimensions, namely 7 self-acceptance dimensions, 7 statements on positive relationships with other people, 7 statements on independence dimension, 7 statements on environmental mastery dimension, 7 statements on life goals dimension, and 7 personal development dimensions. Statements, the total number of statements is 42. Result: Most research results are psychological well-being in the sufficient category (84.5%). Conclusion: It is hoped that this research can be input for students so that they can adapt to a new environment.